GAMBARAN PELAKSANAAN KESEHATAN DAN KESELAMATAN KERJA DI INSTALASI RAWAT INAP RUMAH SAKIT LABUANG BAJI MAKASSAR TAHUN 2024 - Momen Amalia; Upilian Sriyati (Public Health and Medicine Journal, 2025)
Momen Amalia, Title "Overview of the Implementation of Occupational Health and Safety at Labuang Bajı Regional General Hospital, Makassar". Data from the World Health Organization (WHO) of 35 million health workers 3 million exposed to blood pathogens (2 million exposed to HBV virus) 0.9 million exposed to HBC virus and 170,000 exposed to HIV/AIDS virus There can be 15,000 HBC, 70,000 HBV and 1000 HIV cases. More than 90% occur in developing countries 8-12% of hospital workers are sensitive to latex. The probability of HIV transmission after a needle stick injury contaminated with HIV is 4:1000. The risk of HBV transmission after a needle stick injury contaminated with HBV is 27-37:1009 The purpose of this study was to determine the Description of the Implementation of Occupational Health and Safety in the Inpatient Installation at Labuang Bajı Hospital, Makassar. The research method used is a qualitative method with post-positivism or enterpretive techniques and hand observation. Research shows that the implementation of Risk Management has not been carried out optimally. Work accidents that occur and the dangers of risks around the hospital environment and the lack of reports of work accident cases.